Surface remodeling and inversion of cell-matrix interactions underlie community recognition and dispersal in Vibrio cholerae biofilms - Alexis Moreau; Danh T. Nguyen; Alexander J. Hinbest; Anthony Zamora; Ranjuna Weerasekera; Katherine Matej; Xuening Zhou; Sandra Sanchez; Ignacio Rodriguez Brenes; Jung-Shen Benny Tai; Carey D. Nadell; Wai-Leung Ng; et al. (Nature Communications)
Abstract Biofilms are ubiquitous surface-associated bacterial communities embedded in an extracellular matrix. It is commonly assumed that biofilm cells are glued together by the matrix; however, how the specific biochemistry of matrix components affects the cell-matrix interactions and how these interactions vary during biofilm growth remain unclear. Here, we investigate cell-matrix interactions in Vibrio cholerae, the causative agent of cholera. We combine genetics, microscopy, simulations, and biochemical analyses to show that V. cholerae cells are not attracted to the main matrix component (Vibrio polysaccharide, VPS), but can be attached to each other and to the VPS network through surface-associated VPS and crosslinks formed by the protein Bap1. Downregulation of VPS production and surface trimming by the polysaccharide lyase RbmB cause surface remodeling as biofilms age, shifting the nature of cell-matrix interactions from attractive to repulsive and facilitating cell dispersal as aggregated groups. Our results shed light on the dynamics of diverse cell-matrix interactions as drivers of biofilm development.